(3QSGdI aj GdBdI GdQUOjI GdeSeGg PGJ GdcQSis - (3eMeO Hf Ydj GdMejOj GdQhej GdMfaj,J (B1179 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3deG cGfJ PGJ GdcQSi ef BdGJ GdQUOjI cKjQI GdeMUhd HSjQI GdMUhd heY gPG eJQhcg GdYed Hd efSjg GdCUd s
(3BNQgG (B:s
(3dcGf GdHGbi LPQ GdBNQ OhQG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B5 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B331s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B21 ; (3HQhcdeGf (B- (3GdLRA (B2 - (3U (B359 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B133) s
Keywords: (3Gdadcs